(untitled) - Quinn, Barry G. (New York, 2001)
The book does what it sets out to do, and by restricting its scope, is able to focus in-depth on specific aspects of the problem...This book fulfils a role I think primarily as a high-quality expository monograph...It is a nicely presented exposition of one strand of the frequency estimation story, and it is pleasing to see a book devoted to this subject." International Journal of Robust and Nonlinear Control
Keywords: Signal processing,Approximation theory,Xử lý tín hiệu; Mathematics